2010
DOI: 10.12681/mms.86
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Sabella spallanzanii (Polychaeta, Sabellidae) spawning period in the Central Mediterranean Sea: a consequence of climate change?

Abstract: Sabella spallanzanii is a large tubicolous filter feeder polychaete common in the Mediterranean fouling assemblages, where it plays an important role in structuring the community. Its reproductive biology is well known and had has been investigated since 1993. During the past few years, a shift in its reproductive period has been observed. In 2008 the presence of ripe eggs in the females was observed at least two months in advance compared to the past. This was confirmed during the 2009 when spawning and ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…water warming) (Giangrande et al . ). The larval life of S. spallanzanii is longer than that of B. luctuosum (up to 15 days in the first species and only 3 days in the second one) and its population dynamics are easier to follow because of the massive recruitment occurring after spawning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…water warming) (Giangrande et al . ). The larval life of S. spallanzanii is longer than that of B. luctuosum (up to 15 days in the first species and only 3 days in the second one) and its population dynamics are easier to follow because of the massive recruitment occurring after spawning.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, in March it was possible to observe the presence of a great number of juveniles (Giangrande et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies investigating S . spallanzanii reproduction have been done in its native Ionian Sea, Italy [ 47 , 48 ], and in Port Phillip Bay, Australia, where it is invasive [ 49 ]. These studies found that S .…”
Section: Introductionmentioning
confidence: 99%